2006
DOI: 10.1523/jneurosci.2572-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis of Oligodendrocyte Differentiation

Abstract: To better understand the molecular mechanisms governing oligodendrocyte (OL) differentiation, we have used gene profiling to quantitatively analyze gene expression in synchronously differentiating OLs generated from pure oligodendrocyte precursor cells in vitro. By comparing gene expression in these OLs to OLs generated in vivo, we discovered that the program of OL differentiation can progress normally in the absence of heterologous cell-cell interactions. In addition, we found that OL differentiation was unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
353
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(395 citation statements)
references
References 72 publications
38
353
1
3
Order By: Relevance
“…As expected, we found several receptors with known function in rodent OPCs that were highly expressed by their human homologs (Table 2). Among these, we selected CHRM3, muscarinic M 3 R receptor, for functional validation on the basis of particularly high expression in this dataset and strong downregulation during oligodendrocyte differentiation of human CD140a ϩ cells and rat A2B5-sorted progenitors (Dugas et al, 2006). We confirmed differential expression of CHRM3 mRNA in human CD140a …”
Section: Receptor Analysis Reveals Muscarinic Cholinergic Receptor 3 mentioning
confidence: 60%
“…As expected, we found several receptors with known function in rodent OPCs that were highly expressed by their human homologs (Table 2). Among these, we selected CHRM3, muscarinic M 3 R receptor, for functional validation on the basis of particularly high expression in this dataset and strong downregulation during oligodendrocyte differentiation of human CD140a ϩ cells and rat A2B5-sorted progenitors (Dugas et al, 2006). We confirmed differential expression of CHRM3 mRNA in human CD140a …”
Section: Receptor Analysis Reveals Muscarinic Cholinergic Receptor 3 mentioning
confidence: 60%
“…Transcriptional regulation plays an important role in the differentiation of OL lineage cells from initial GPCs to fully mature myelinating OLs (Dugas et al, 2006;Nicolay et al, 2007). Previous studies showed that a pair of related basic helix-loop-helix transcription factors, Olig1 and Olig2, is essential for generating OL lineage cells (Lu et al, 2000;Zhou and Anderson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies identified phosphodiesterase-Iα/autotaxin (PD-Iα/ATX), also designated pyrophosphatase/phosphodiesterase 2 (NPP2), as a protein that is released by post-migratory, premyelinating oligodendrocytes during the developmental stages of initial myelination (Fuss et al, 1997;Fox et al, 2003; see also Dugas et al, 2006;Nielsen et al, 2006;Savaskan et al, 2006). Functionally, PD-Iα/ATX possesses active adhesion-antagonizing, i.e.…”
Section: Introductionmentioning
confidence: 99%